Sustainable manufacturing for Indonesian small- and medium-sized enterprises (SMEs): the case of remanufactured alternators - Fatimah, Arifatul; Biswas, Wahidul; Mazhar, Muhammad Ilyas; Islam, Mohammad Nazrul (Springer, 2013)
Achieving sustainability is a great challenge for most of the Indonesian manufacturingsmall- and medium-sized enterprises (SMEs). Remanufacturing has been considered tobe a key strategy to attain sustainable manufacturing by maximising the use of oldcomponents and minimising landfill size and energy usage. However, SMEs, which areundoubtedly the engine of the Indonesian manufacturing industry, do not haveadequate experience, skill, resource, technology and financial support in theremanufacturing area. This paper proposes a new concept for sustainablemanufacturing assessment framework through remanufacturing strategies inIndonesian SMEs. In this sustainable manufacturing assessment framework, the existingremanufactured products are assessed using sustainable manufacturing criterion (e.g.reliability, life cycle cost, employment opportunity and greenhouse gases). Thisframework identifies improvement opportunities, including eco-efficiency, cleanerproduction and green technology to make existing remanufactured productstechnically, economically, environmentally and socially sustainable. The sustainability ofremanufactured alternators produced by Indonesian SMEs has been assessed tovalidate the aforementioned sustainable manufacturing assessment framework.